The Degree of Educational Supervisor application to its supervisal roles in Damascus city in the light of the comprehensive quality standards . (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present research aims to define the educational supervisor degree to its supervisal roles in Damascus city in the light of comprehensive quality standards , and show the difference among the educational supervisors points of view in the same field according to the varieties ofsex , scientific qualification and the years of experience in the educational supervisor. The researcher used the analytic descriptive method and made a questionnaire consisted of ( 32 )points applied on a sample of educational supervisors who work in Damascus city reached to 30 supervisors . The results showed that the educational supervisor application degree to the supervisal roles in the light of the comprehensive quality standards were in the middle degree and the order in the fields of education supervisor application was descending as follows : Focus on teachers roles , the effective educational leadership , the interest in teamwork , evaluation and continuous improving . The results also showed differences of statistic significance among the educational supervisors estimates in relation with the degree of the educational supervisor application to the supervisal roles in schools according to the varieties of sex , scientific qualification and the years of experience in the educational supervision .